Isolation of Newcastle Disease Viruses of High Virulence in Unvaccinated Healthy Village Chickens in South India - Ananth, R.; Kirubaharan, J. John; Priyadarshini, M.L.M.; Albert, A. (International Journal of Poultry Science, 2008)
Three isolates of Newcastle disease virus obtained from normal village chickens, which were never vaccinated against Newcastle disease were characterized. These isolates namely D8, D53 and D58 were found to have an ICPI value of 1.59, 0.50 and 0.14 respectively. The deduced amino acid sequence at the FPCS of these three isolates between positions 112 and 119 were G-R-R-Q-K-R-F-I-G- -G-R-R-Q-K-R-F-I-G- and – G-G-R-Q-G-R-L-I-G- respectively. The two isolates namely D8 and D53 had phenylalanine (F) residue at position 117, confirming their high virulence to chicken, whereas the isolate D58 had leucine (L) at 117 confirming their low virulence to chicken. The existence of NDV with high ICPI confirms the circulation of virulent NDV in village chicken raised in the backyard, which could be a threat to commercial chicken.